HUBUNGAN ANTARA PERILAKU MASYARAKAT DAN TINGKAT PENCEMARAN TERHADAP KUALITAS BAKTERIOLOGIS AIRBERDASARKAN PERHITUNGAN JUMLAH Coliform DAN IDENTIFIKASI Escherichia coli PADA AIR SUMUR GALI DIKELURAHAN SUMURBATU BANTARGEBANG BEKASI PERIODE FEBRUARI 2014 - Amanda Friska Rismayanti (2014)
Water is an important source in life. Existence of bacteria in water can lead to bacteriological contamination and change water's quality and it caused by some factor including behavior of people and the risk level of dug-well water contamination. The purpose of this study is to find out relationship between behavior of household water users and the risk of contamination with bacteriological quality of water. The type of research is analytical descriptive with cross sectional approach and used consecutive sampling. All of sample were taken from 46 dug-well water and respondents. The results showed that the average total number of Coliform reaches 552,79 Coliform/100ml with class C water quality as poor category and 9 of 46 dug-well water sample consist Escherichia coli. Based on chi square statistical test, there is a significant relationship between behavior of household water user (p=0,001) and the risk of contamination (p=0,012) with bacteriological quality of dug-well water. Results of multiple logistic regression statistical test showed that behavior of water user is more affecting to change bacteriological quality of water by increase the number of Coliform (p=0,031; OR:8,351) with probability number up to 37%.